1982
DOI: 10.1002/for.3980010203
|View full text |Cite
|
Sign up to set email alerts
|

Subjective confidence in forecasts

Abstract: Forecasts have little value to decision makers unless it is known how much confidence to place in them. Those expressions of confidence have, in turn, little value unless forecasters are able to assess the limits of their own knowledge accurately Previous research has shown very robust patterns in the judgements of individuals who have not received special training in confidence assessment: Knowledge generally increases as confidence increases. However, it increases too swiftly, with a doubling of confidence b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(71 citation statements)
references
References 37 publications
2
68
1
Order By: Relevance
“…However, it is an inevitable problem that knowledge questions given to professionals in their areas of expertise are likely to be interpreted as tests of primary knowledge, and thus ability. Previous research has indicated that experts are, in most cases, equally prone to biased judgments (Fischhoff and MacGregor, 1982). But such an assertion overlooks the fact that the job of experts is typically to forecast the value of a realized stochastic variable (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is an inevitable problem that knowledge questions given to professionals in their areas of expertise are likely to be interpreted as tests of primary knowledge, and thus ability. Previous research has indicated that experts are, in most cases, equally prone to biased judgments (Fischhoff and MacGregor, 1982). But such an assertion overlooks the fact that the job of experts is typically to forecast the value of a realized stochastic variable (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The overconfidence bias is one in which people often tend to be more confident than they have a right to be in the accuracy of their forecast or diagnosis (Bornstein & Zickafoos, 1999;Fischoff & MacGregor, 1982;Kahneman, 2011;Wickens et al, 2013). This is often as true of experts as of novices (Kahneman, 2011;Taleb, 2007).…”
Section: Heuristics and Biases In Situation Assessment Or Diagnostic mentioning
confidence: 99%
“…I have replicated this study many times and obtained similar results. As people gain expertise in an area, their tendency toward overconfidence increases [Fischhoff and MacGregor 1982]. 1 suggest that you ignore confidence claims by individuals, except where feedback about outcomes is readily available and easy to summarize.…”
Section: Combinations Of Forecastsmentioning
confidence: 99%